17β-Estradiol Promotes Tumorigenicity Through an Autocrine AREG/EGFR Loop in ER-α-Positive Breast Cancer Cells - Sun Young Yoon; Yisun Jeong; Jai Min Ryu; Se Kyung Lee; Byung Joo Chae; Jonghan Yu; Seok Won Kim; Seok Jin Nam; Sangmin Kim; Jeong Eon Lee (Cells)
We previously reported that the level of EGFR expression is directly associated with the survival rate of estrogen receptor-positive (ER+) breast cancer patients. Here, we investigated how ER activation by 17β-estradiol (E2), the most potent form of estrogen, affects the expression or activity of EGFR or EGFR-related genes in ER+ breast cancer cells. As expected, E2 enhanced cell proliferation, the induction of S phase, and tumor growth in ER+ breast cancer models. E2 also increased the expression of secretory proteins, including amphiregulin (AREG), angiogenin, artemin, and CXCL16. We focused on AREG, which is a ligand of the epidermal growth factor receptor (EGFR). The levels of AREG expression were positively correlated with ESR1 expression. Our results also showed higher AREG mRNA expression levels in ER+ breast cancer cells than in ER- breast cancer cells. We treated ER+ breast cancer cells with lapatinib to inhibit the AREG/EGFR signaling pathway and then completely inhibited E2-induced cell proliferation and S-phase induction. Similar to the lapatinib treatment, cell proliferation, S-phase induction, cell migration, and tumor growth were suppressed by AREG knockdown. Taken together, we demonstrated that the induction of AREG by E2 contributes to EGFR activation, which then affects cell proliferation and tumor growth. Therefore, we suggest that AREG acts as an intermediary between EGFR and ER and targeting both ERs and EGFRs through combination therapy could prevent tumor progression in EGFR+ ER+ breast cancer patients.